PENERAPAN PRINSIP KEADILAN DALAM PENYELESAIAN SENGKETA TANAH DALAM RANGKA MEWUJUDKAN KESEJAHTERAAN MASYARAKAT - Annastasya Ria Octary; Niru Anita Sinaga (LEX LAGUENS: Jurnal Kajian Hukum dan Keadilan, 2026)
Land disputes remain a persistent and fundamental issue in Indonesia, particularly in rural areas where land functions not only as a source of livelihood but also as a marker of social identity. These conflicts often extend beyond legal boundaries and encompass complex social, economic, and political dimensions. This article aims to examine how the application of the principle of justice in resolving land disputes can contribute to achieving community welfare, while also identifying the obstacles that hinder its effective implementation. The research employs a normative juridical method using a statute approach, by analyzing legal frameworks such as Law Number 5 of 1960 on the Basic Agrarian Principles, Government Regulation Number 24 of 1997 on Land Registration, and Law Number 11 of 2020 on Job Creation. Findings reveal that the application of justice in land dispute resolution has yet to function optimally. Key obstacles include limited public access to legal mechanisms, overlapping land administration systems, weak integrity among local officials, and low legal literacy at the grassroots level. The study concludes that substantive justice must serve as the foundation for resolving land conflicts, ensuring that the law acts not merely as an instrument of power but as a means of protecting rights and improving public welfare. A fair, transparent, and pro-people agrarian reform is essential to realizing an equitable land governance system in Indonesia.